Effectiveness of Liquid Organic Fertilizer Made from Sugarcane Bagasse and Rice Water on Green Spinach Plants (Amaranthus hybridus L.) - Taufiqurrohman, Haikal; Dewi, Sari Kusuma (LenteraBio : Berkala Ilmiah Biologi, 2024)
Bagasse and rice washing water contain organik elements that are commonly found in the community and have not been utilized optimally. One of the vegetables that contain Fe iron is spinach which can be used as an antioxidant. This study aimed to determine the nutrient content of liquid organic fertilizer (POC) bagasse and rice water, and determine the effectiveness and optimum concentration on the growth of green spinach plants (Amaranthus hybridus L.). This study used Randomized Block Design with one factor in the treatment, namely the application of liquid organik fertilizer based on bagasse and rice washing water on green spinach (Amaranthus hybridus L), with 4 treatments together with 6 replications, as a result 24 experimental units were found to be carried out. The POC concentrations used were 50 ml/L, 75 ml/L, and 100 ml/L. Data on the nutrient content of liquid organik fertilizers were analyzed through laboratory tests, while data on the growth of green spinach plants were analyzed using the F test (ANOVA). Data showing significant differences in the results of the treatment were further analyzed using Duncan's test at a level of 0.05. The results showed that POC in treatment C with a concentration of 75 ml/L and treatment D with a concentration of 100 ml/L of water were optimal and effective treatments for the growth of green spinach plants.